Effect of Kangaroo mother care in reducing pain due to heel prick among preterm neonates: a crossover trial. (March 2014) - Chidambaram, Ambika Gnanam; Manjula, S.; Adhisivam, B.; Vishnu Bhat, B.
Abstract Background: Preterm neonates undergo several painful procedures in NICU including heel prick for blood sugar monitoring. Nonpharmacological interventions have been tried to decrease this procedural pain. There are only few studies on Kangaroo mother care (KMC) in reducing pain among preterm neonates. Method: This crossover trial was conducted at a tertiary care teaching hospital in south India. Premature Infant Pain Profile (PIPP) related to heel prick was assessed in 50 preterm neonates undergoing KMC and compared with 50 preterm babies without KMC. Results: PIPP scores at 15 minutes and 30 minutes after heel prick were significantly less in KMC group compared to control group. Mean PIPP difference between baseline and 30 minutes after heel prick was also significantly low in KMC group compared to control group. Conclusion: KMC is effective in reducing pain due to heel prick among preterm babies.